Progress in heterocyclic chemistry. Vol. 16, A critical review of the 2003 literature preceded by two chapters on current heterocyclic topics - Gribble, Gordon W.; Joule, J. A. (John Arthur); ScienceDirect eBooks (Oxford : Elsevier, 2004)
This is the sixteenth annual volume of Progress in Heterocyclic Chemistry, and covers the literature published during 2003 on most of the important heterocyclic ring systems. This volume opens with two specialized reviews. The first covers 'Lamellarins: Isolation, activity and synthesis' a significant group of biologically active marine alkaloids and the second discusses 'Radical Additions to Pyridines, Quinolines and Isoquinolines'. The remaining chapters examine the recent literature on the common heterocycles in order of increasing ring size and the heteroatoms present.
Chapter 1: Lamellarins: Isolation, activity and synthesis. -- Chapter 2: Radical additions to pyridines, quinolines and isoquinolines. -- Chapter 3: Three-membered ring systems. -- Chapter 4: Four-membered ring systems. -- Chapter 5: Five-Membered Ring Systems -- Part 1. Thiophenes & Se, Te Analogs. -- Part 2. Pyrroles and Benzo Derivatives. -- Part 3. Furans and Benzofurans. -- Part 4. With More than One N Atom. -- Part 5. With N & S (Se) Atoms. -- Part 6. With O & S (Se, Te). -- -- Part 7. With O & N. -- Chapter 6: Six-Membered Ring Systems -- Part 1. Pyridines and Benzo Derivatives. -- Part 2. Diazines and Benzo Derivatives. -- -- Part 3. Triazines, Tetrazines and Fused Ring Polyaza Systems. -- Part 4. With O and/or S Atoms. -- Chapter 7: Seven-Membered Ring Systems. -- Chapter 8: Eight-Membered and Larger Ring Systems. -- Index.
Includes index.
Print version record.
Elsevier
Keywords: Heterocyclic chemistry; Heterocyclic chemistry; Electronic books